2010
DOI: 10.1200/jco.2009.25.6941
|View full text |Cite|
|
Sign up to set email alerts
|

Hypofractionated Stereotactic Radiation Therapy: An Effective Therapy for Recurrent High-Grade Gliomas

Abstract: Purpose Salvage options for recurrent high-grade gliomas (HGGs) are limited by cumulative toxicity and limited efficacy despite advances in chemotherapeutic and radiotherapeutic techniques. Previous studies have reported encouraging survival results and favorable toxicity with fractionated stereotactic radiotherapy, and small studies have shown similar benefit using a shortened course of hypofractionated stereotactic radiation therapy (H-SRT). We sought to determine the efficacy and toxicity profile of H-SRT a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
246
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 311 publications
(264 citation statements)
references
References 38 publications
14
246
4
Order By: Relevance
“…The role of re-irradiation is uncertain, including the role of amino acid positron emission tomography (PET) for target delineation, and multiple fractionation regimens have been proposed, e.g., from 6 x 5 Gy to 18 x 2 Gy. 44,45 The three strategies of medical treatment for glioblastoma recurring after TMZ/RT→TMZ most commonly used across Europe include nitrosourea-based regimens, alternative dosing regimens of TMZ, and bevacizumab. The activity of CCNU has been confirmed in the standard arms of randomized trials exploring the activity of the protein kinase C-β inhibitor, enzastaurin, 46 or the vascular endothelial growth factor (VEGF) receptor inhibitor, cediranib, 47 with progression-free survival rates at 6 months of 20%.…”
Section: Glioblastoma (Who Grade Iv)mentioning
confidence: 99%
“…The role of re-irradiation is uncertain, including the role of amino acid positron emission tomography (PET) for target delineation, and multiple fractionation regimens have been proposed, e.g., from 6 x 5 Gy to 18 x 2 Gy. 44,45 The three strategies of medical treatment for glioblastoma recurring after TMZ/RT→TMZ most commonly used across Europe include nitrosourea-based regimens, alternative dosing regimens of TMZ, and bevacizumab. The activity of CCNU has been confirmed in the standard arms of randomized trials exploring the activity of the protein kinase C-β inhibitor, enzastaurin, 46 or the vascular endothelial growth factor (VEGF) receptor inhibitor, cediranib, 47 with progression-free survival rates at 6 months of 20%.…”
Section: Glioblastoma (Who Grade Iv)mentioning
confidence: 99%
“…Radiosurgery is less frequently used in glioblastoma. As favorable variables for selecting patients likely to benefit from re-irradiation again general prognostic factors such as young age, high KPS or small tumor size have been proposed [32,[34][35][36][37]. Different reports exist regarding the preferred time interval to initial radiation for benefit from re-irradiation, favoring either an interval of less than 6 months [35] or more than 6 or even 12 months [37,38].…”
Section: Repeat Radiotherapymentioning
confidence: 99%
“…However, different methods of documenting tumor status make comparisons across studies difficult. For instance, Fogh, et al [19] reported stable disease in 60% of patients based on the three-month follow-up MRI scan. The present study uses the last available follow-up MRI scan to determine disease state.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, HFSRT has emerged as a noninvasive method to deliver a high dose of radiation to the tumor site. In the treatment of recurrent GBM, numerous studies have documented a survival advantage on the use of HFSRT [10][11][12][13][14][15][16][17][18] and HFSRT in combination with chemotherapy [19][20][21][22][23][24]. Specifically, Iuchi, et al [25] has shown that a single dose of more than 20 Gy is able to achieve durable local control in 72% of patients; however, radiation necrosis (RN) was observed in 43% of patients.…”
Section: Introductionmentioning
confidence: 99%